2016
DOI: 10.1002/cphc.201501184
|View full text |Cite
|
Sign up to set email alerts
|

Towards Redox‐Driven Unidirectional Molecular Motion

Abstract: Redox-driven molecular motion is an attractive alternative to light-driven processes. Here, the ability of an overcrowded alkene-based unimolecular light-driven rotary motor (A) to be driven by oxidation/reduction cycles is explored. We show that two-electron oxidation of A is followed by irreversible deprotonation and reduction to form a monocationic species D(+) , in which the stereogenic center is lost. This latter species was isolated through preparative electrolysis and its structure was confirmed by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A major hurdle to overcome in the development of electrochemically-driven molecular rotors is the chemical stability of these compounds under oxidative conditions. 114 Almost two decades of research since the initial discovery of the light-driven unidirectional molecular rotor led to the development of large variety of molecular motors with different structure and function, and with a higher degree of control on their behaviour. The main questions which need to be addressed will be how the generated molecular motion can be translated into mesoscopic or even macroscopic directional motion and how this motion can be harnessed to achieve functions such as transport.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…A major hurdle to overcome in the development of electrochemically-driven molecular rotors is the chemical stability of these compounds under oxidative conditions. 114 Almost two decades of research since the initial discovery of the light-driven unidirectional molecular rotor led to the development of large variety of molecular motors with different structure and function, and with a higher degree of control on their behaviour. The main questions which need to be addressed will be how the generated molecular motion can be translated into mesoscopic or even macroscopic directional motion and how this motion can be harnessed to achieve functions such as transport.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…In the recent attempt of Logtenberg et al to deviseaunidirectionale lectrochemically driven molecular motor based on as econd generation motor,i tw as observedt hat deprotonation at the stereogenic centerresults in double bond migration inside the upper rotor half and this constitutes the major degradationp athway because it leads to ar elease of the strain aroundt he overcrowdedd ouble bond axle (Scheme1). [34] In that study,t he molecular motor 1 was electrochemically oxidized to dication 2.H owever,i nt he presence of water, 2 underwenti rreversible deprotonation to restorea romaticity of the naphthalene moiety as confirmed by X-ray structure determination. The formation of side product 3 hindered further application of the compound 1 as an electrochemically driven unidirectionalm olecularm otor.P otentially blockingt his position with an additional substituent and thus preventing the undesired deprotonation step coulda lleviate this issue and allow for the construction of ar eversible redox-active and unidirectional molecular motor.…”
Section: Introductionmentioning
confidence: 82%
“…In the recent attempt of Logtenberg et al. to devise a unidirectional electrochemically driven molecular motor based on a second generation motor, it was observed that deprotonation at the stereogenic center results in double bond migration inside the upper rotor half and this constitutes the major degradation pathway because it leads to a release of the strain around the overcrowded double bond axle (Scheme ) . In that study, the molecular motor 1 was electrochemically oxidized to dication 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations